2007
DOI: 10.1111/j.1365-2621.2006.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using interesterified and non‐interesterified corn and palm oil blends on quality and fatty acid composition of Turkish White cheese

Abstract: Chemically interesterified blends (CIB) and non-interesterified blends (NIB) of corn and palm oils (75%w/ 25%w) were studied in the production of Turkish White cheese (TWC) to modify the fatty acid composition of traditional product. Milk fat (3%) was replaced by CIB and NIB for 25%, 50%, 75% and 100%. All cheese groups were ripened at 5°C for 90 days. Samples were taken from each group after 3, 30, 60 and 90 days and analysed for their basic composition, lipolysis and proteolysis. CIB-incorporated cheeses sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…TCA-SN values express small molecules of peptides (lower than 20 amino acid residues) and free amino acids. TCA-SN components, which occur as a result of proteinase activity, are used to determine the proteolysis level (Javidipour and Tuncturk 2007). At the end of ripening, TCA-SN values of samples increased by 36.7-77.8 % when compared with those at the beginning of ripening (1 day).…”
Section: Composition Of Cheesementioning
confidence: 99%
See 1 more Smart Citation
“…TCA-SN values express small molecules of peptides (lower than 20 amino acid residues) and free amino acids. TCA-SN components, which occur as a result of proteinase activity, are used to determine the proteolysis level (Javidipour and Tuncturk 2007). At the end of ripening, TCA-SN values of samples increased by 36.7-77.8 % when compared with those at the beginning of ripening (1 day).…”
Section: Composition Of Cheesementioning
confidence: 99%
“…Hovewer, some vegetable oils have only limited applications in their original forms because of their specific chemical composition (Javidipour and Tuncturk 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Interesterification which mainly based on rearranging the distribution of fatty acids on the glycerol backbone without changing their chemical composition have been used to improve the cold spreadability of butterfat-canola oil blends (Rousseau and Marangoni 1999) and the production of margarine (Petrauskaite et al 1998), cheese (Javidipour and Tuncturk 2007), shortening (Öztürk et al 2008;Rodriguez et al 2001), frankfurter (Vural et al 2004;Vural and Javidipour 2002) and Turkish-type salami (Javidipour et al 2005;Javidipour and Vural 2002). Dogan et al (2007) successfully made cakes with zero-TFA by using in-es cottonseed (CO) and palm oil (PO) blends without any considerably adverse change in sensorial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interesterification has been employed to improve the cold spreadability of butterfat–canola oil blends (Marangoni and Rousseau 1998; Rousseau and Marangoni 1999) and the production of margarine (Petrauskaite et al. 1998), cheese (Yu and Hammond 2000; Javidipour and Tuncturk 2007), shortening (Rodriguez et al. 2001; Dogan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Interesterification does not change the degree of unsaturation of the fatty acids as it transfers them from one position to another and does not create trans isomers (Stauffer 1996;Shahidi et al 1997;Norizzah et al 2004). Recently, interesterification has been employed to improve the cold spreadability of butterfat-canola oil blends (Marangoni and Rousseau 1998;Rousseau and Marangoni 1999) and the production of margarine (Petrauskaite et al 1998), cheese (Yu and Hammond 2000;Javidipour and Tuncturk 2007), shortening (Rodriguez et al 2001;Dogan et al 2006), frankfurter Vural et al 2004) and Turkish-type salami Javidipour et al 2005). However, Park et al (1983) found that the loss of tocopherols accelerated the autoxidation of randomized soybean oil, and Basturk et al (2007) indicated that based on peroxide and anisidine values and reaction rate constants, the oxidative stability of in-es CO, PO and soybean oils were higher than their non-in-es counterparts.…”
Section: Introductionmentioning
confidence: 99%